SYSTEMATIC LITERATURE REVIEW: THE EFFECTIVENESS OF THE SELF-ORGANIZED LEARNING ENVIRONMENT (SOLE) MODEL IN SCIENCE EDUCATION - Gilang Putri; Irwandani Irwandani; Nur Hidayah (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2025)
This study aimed to evaluate the effectiveness of the Self-Organized Learning Environment (SOLE) model in science education. The method used is a SLR based on the PRISMA guidelines, combined with a thematic approach. Data were analyzed from articles indexed in the Scopus and Sinta databases. The analysis results indicate a rising trend in the number of publications on the SOLE model, particularly in the field of chemistry, during the period from 2020 to 2024. Several frequently cited authors, including Sri Suciati and Dewi Sri Matovani, have made significant contributions to the development of this model. The main findings show that the implementation of the SOLE model effectively improves students’ science learning outcomes, including concept comprehension, learning motivation, academic achievement, and metacognitive skills. Based on these results, this study provides a strong foundation for the development and implementation of the SOLE learning model across various educational levels.